Analysis of temporal change in delivery of ecosystem services over 20 years at long term monitoring sites of the UK Environmental Change Network. (September 2016) - Dick, J.; Andrews, C.; Beaumont, D.A.; Benham, S.; Dodd, N.; Pallett, D.; Rose, R.; Scott, T.; Smith, R.; Schäfer, S.M.; Turner, A.; Watson, H.
Abstract: The drivers and pressures experienced by farmland, forestry and upland sites in the UK Environmental Change Network (ECN) over the last 20 years are reported through the lens of recognised approaches to the assessment of ecosystem service delivery. Temporal trends in ecosystem service delivery were examined using two methods: qualitative narratives and quantitative scoring of ecosystem service delivery according to land cover. While all sites included in this study are within the same national governance unit (i.e. UK), individual local management decisions were the main agents driving change, influenced by EU and national policies. Gradual change in focus from provisioning to cultural ecosystem services was a persistent trend across most sites, and apparent in both methods. There was generally no net loss in regulating services at the sites. The two methods were subjective but as data were not available for the breadth of ecosystem services present at the sites between 1993 and 2012, it was concluded that it is more informative for holistic assessments to draw on qualitative expert opinion than to ignore less quantifiable services such as many of the cultural services.